The Development of Knowledge Enrichment Books Concerning Ice and Snow Physical Studies for High-School Students - Slamet Maulana; Desnita Desnita; Raihanati Raihanati (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2018)
This research aims to develop a knowledge-enrichment physics book of ice and snow that is worthy of use as an enrichment material on physics subject. This research is a research and development with an ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. The developed book referred from the Central of Curriculum and Book guideline so that the developed book can be recommended as enrichment material for high-school students. The developed book uses communicative language, attractive illustrations, and information concerning ice and snow with updated science knowledge. The result by physics expert on the developed enrichment book is 94.12% with a category